Enrofloxacin and Roundup® interactive effects on the aquatic macrophyte Elodea canadensis physiology. (June 2019) - Gomes, Marcelo Pedrosa; Tavares, Davi Santos; Richardi, Vinícius Sobrinho; Marques, Raizza Zorman; Wistuba, Natalia; Moreira de Brito, Júlio César; Soffiatti, Patrícia; Sant'Anna-Santos, Bruno Francisco; Navarro da Silva, Mário Antônio; Juneau, Philippe
Abstract: The co-occurrence of aquatic contaminants, such as antibiotics and herbicides, has motivated investigations into their interactive effects on aquatic organisms. We examined the combined effects of environmental concentrations of the antibiotic Enrofloxacin (Enro; 0–2.25 μg l −1 ) and Roundup Original DI (Roundup ® ; 0–0.75 μg active ingredient l −1 ), a glyphosate based-herbicide, on Elodea canadensis . Enro alone was not toxic, but the plants were highly sensitive to Roundup ® whose toxicity is related to the induction of oxidative stress. The metabolism of Enro by plants into Ciprofloxacin (Cipro) was observed, and although former is not phytotoxic, oxidative events associated with Cipro generation were observed. The activity of cytochrome P450 was shown to be involved in Enro degradation in E. canadensis . As a cytochrome P450 inhibitor, Roundup ® decreases Enro metabolism in plants. Enro, in turn, increases glyphosate uptake and toxicity, so that Enro and Roundup ® have synergistic effects, disrupting the physiological processes of E. canadensis . Our results suggest E. canadensis as a potential candidate for the reclamation of Enro in contaminated waters, but not for Roundup ® due to its high sensitivity to that herbicide. Graphical abstract: Image 1 Highlights: Cytochrome P450 activity was involved in Enrofloxacin degradation in E. canadensis . Roundup ®, a glyphosate-based herbicide, acts as a Cytochrome P450 inhibitor. Roundup ® decreases Enrofloxacin metabolism in plants. Enrofloxacin increases glyphosate uptake and toxicity. Enrofloxacin and Roundup ® have synergistic effects on E. canadensis physiology. Abstract : The activity of cytochrome P450 was shown to be involved in Enrofloxacin degradation and toxicity in E. canadensis .